Deviant behavior - Humphrey, John A. (Upper Saddle River, N.J. : Pearson Education, Inc., 2006)
"Interest in deviant behavior is self-evident, not only within the United States, but across the globe. This contemporary text not only fosters that interest, but provides readers with empirically verifiable information and a range of theoretical perspectives on deviant behaviors that will challenge students to develop a global perspective on emerging social issues." "Portraits of social deviants introduce each chapter of the text, illustrating the social context of the deviants' behavior, clarifying the most recent findings, and providing an assessment of the key theories to explain and predict future deviant behavior. Timely issues such as terrorism, international organized crime, white-collar crime, mental illness, drug trafficking, cyberdeviance, and sexual exploitation are addressed.".
"Firmly grounded in traditional sociological and social psychological understandings of deviant behavior and social control, this book presents a challenge to students interested in exploring the emerging shape of deviance in the 21st century. The study of deviant behavior is undergoing a radical transformation. Deviant Behavior encourages students to become engaged in that process."--BOOK JACKET.
1. Introduction to the study of deviant behavior -- 2. Theories of individual forms of deviant behavior -- 3. Theories of the variations in rates of deviant behavior -- 4. Homicide -- 5. Domestic violence -- 6. Suicide and life-threatening behaviors -- 7. Mental illness -- 8. Alcohol abuse -- 9. Illicit drug use -- 10. Sexual offending -- 11. Property crimes -- 12. White-collar and organized crime -- 13. Cyberdeviance -- 14. Positive deviance -- 15. Extreme forms of everyday behaviors : exercising, working, and Web surfing -- 16. Terrorism.
Includes bibliographical references and index.
Keywords: Deviant behavior